Saturation Policing and Robberies: Quasi-Experimental Evidence about the Effect of Sudden and Quick Operations. (3rd July 2019) - Cid, Alejandro
Abstract: Latin America is the only region in the world where lethal violence increased in the first decade of the 21 st century, and its citizens identified crime and violence as their main concern. Though previous literature shows promising results of saturation policing on crimes, little rigorous evidence exists on the impact of these strategies on the cited region. I study the effects of the implementation of a special saturation policing operation in Uruguay, a Latin-American country that has experienced a huge increase in crime in the last decade. I employ a difference-in-difference approach exploiting the fact that the saturation operation was applied only in the capital of Uruguay due to restriction of resources. I find that the capital experienced a reduction between 20% and 30% in robberies in comparison with the control cities.